Produktivitas dalam Perspektif Ekonomi Islam - Anwar, Moch. Khoirul (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2020)
Islam teaches productivity. However, there are still many Muslims live below the poverty line. This paper aims to analyze the productivity concept in the Islamic Economics perspective. This paper used the library research method, which focuses on various literature that discussed productivity in the Islamic Economics perspective. The data was analyzed using Content Analysis to identify the specific characteristics of the message or data that have been collected. The result showed that Islamic Economics teaches and pays attention to productivity, among them is making the best use of time. Productivity in Islamic economics is not only measured by the results of material (physical) but also immaterial (spiritual) and its orientation not only about the happiness in the world, but also the hereafter.